Oxygen Pathway Limitations in Patients With Chronic Thromboembolic Pulmonary Hypertension. Issue 21 (15th April 2021) - Howden, Erin J.; Ruiz-Carmona, Sergio; Claeys, Mathias; De Bosscher, Ruben; Willems, Rik; Meyns, Bart; Verbelen, Tom; Maleux, Geert; Godinas, Laurent; Belge, Catharina; Bogaert, Jan; Claus, Piet; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Exertional intolerance is a limiting and often crippling symptom in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Traditionally the pathogenesis has been attributed to central factors, including ventilation/perfusion mismatch, increased pulmonary vascular resistance, and right heart dysfunction and uncoupling. Pulmonary endarterectomy and balloon pulmonary angioplasty provide substantial improvement of functional status and hemodynamics. However, despite normalization of pulmonary hemodynamics, exercise capacity often does not return to age-predicted levels. By systematically evaluating the oxygen pathway, we aimed to elucidate the causes of functional limitations in patients with CTEPH before and after pulmonary vascular intervention. Methods: Using exercise cardiac magnetic resonance imaging with simultaneous invasive hemodynamic monitoring, we sought to quantify the steps of the O2 transport cascade from the mouth to the mitochondria in patients with CTEPH (n=20) as compared with healthy participants (n=10). Furthermore, we evaluated the effect of pulmonary vascular intervention (pulmonary endarterectomy or balloon angioplasty) on the individual components of the cascade (n=10). Results: Peak Vo 2 (oxygen uptake) was significantly reduced in patients with CTEPH relative to controls (56±17 versus 112±20% of predicted; P <0.0001). The difference was attributable to impairments in multiple steps of the O2 cascade, including O2 delivery (product of cardiac output and arterial O2 content), skeletal muscle diffusion capacity, and pulmonary diffusion. The total O2 extracted in the periphery (ie, ΔAVo 2 [arteriovenous O2 content difference]) was not different. After pulmonary vascular intervention, peak Vo 2 increased significantly (from 12.5±4.0 to 17.8±7.5 mL/[kg·min]; P =0.036) but remained below age-predicted levels (70±11%). The O2 delivery was improved owing to an increase in peak cardiac output and lung diffusion capacity. However, peak exercise ΔAVo 2 was unchanged, as was skeletal muscle diffusion capacity. Conclusions: We demonstrated that patients with CTEPH have significant impairment of all steps in the O2 use cascade, resulting in markedly impaired exercise capacity. Pulmonary vascular intervention increased peak Vo 2 by partly correcting O2 delivery but had no effect on abnormalities in peripheral O2 extraction. This suggests that current interventions only partially address patients' limitations and that additional therapies may improve functional capacity.